Characteristics of test items focusing on meaningful learning: a case study in pre-vocational geography education in the Netherlands - Erik BIJSTERBOSCH; Tine BÉNEKER; Joop van der SCHEE; Wilmad KUIPER (European Journal of Geography)
Summative assessments tend to encourage students’ rote learning rather than meaningful learning. Yet, summative assessments might contribute to meaningful learning when they meet certain criteria, such as the use of test items and corresponding scoring rubrics that appeal to higher cognitive processes and to divergent assessment. In 2016, a small-scale study was conducted with six geography teachers of pre-vocational education to examine which type of test items and accompanying scoring rubrics are feasible and practical to support meaningful learning and which strategies can scaffold both teachers and students. The results showed that teachers were most positive about pre-structured test items. Both teachers and students were also positive about the application of a flow chart to scaffold students in answering the test items. The results showed that teachers encountered problems in scoring open, more complex test items focusing on evaluating and creating